Preoperative diagnosis of solitary pulmonary nodules with a novel hematological index model based on circulating tumor cells - Zhou, Qiuxi; He, Qiao; Peng, Ling; Huang, Yecai; Li, Kexun; Liu, Kun; Li, Da; Zhao, Jing; Sun, Kairong; Li, Aoshuang; He, Wenwu (Frontiers in Oncology, 2023)
Objective: Preoperative noninvasive diagnosis of the benign or malignant solitary pulmonary nodule (SPN) is still important and difficult for clinical decision and treatment. This study aimed to assist in the preoperative diagnosis of benign or malignant SPN by blood biomarkers. Methods: Two hundred and eighty-six patients were recruited for this study. The serum FR+CTC, TK1, TP, TPS, ALB, Pre-ALB, ProGRP, CYFRA21-1, NSE, CA50, CA199, and CA242 were detected and analyzed. Results: In the univariate analysis, Age, FR+CTC, TK1, CA50, CA19.9, CA242, ProGRP, NSE, CYFRA21-1, and TPS showed the statistical significance of correlation with malignant SPNs (P<0.05). The highest performing biomarker is FR+CTC (odd ratio [OR], 4.47; 95%CI: 2.57-7.89; P<0.001). The multivariate analysis identified that age (OR, 2.69; 95%CI: 1.34-5.59, P=0.006), FR+CTC (OR, 6.26; 95%CI: 3.09-13.37, P＜0.001), TK1 (OR，4.82; 95%CI: 2.4-10.27, P＜0.001) and NSE (OR, 2.06; 95%CI: 1.07-4.06, P=0.033) are independent predictors. A predicting model based on age, FR+CTC, TK1, CA50, CA242, ProGRP, NSE and TPS was developed and presented as a nomogram, with a sensitivity of 71.1% and specificity of 81.3%, and the AUC was 0.826 (95% CI: 0.768-0.884). Conclusions: The novel predicting model based on FR+CTC showed much stronger performance than any single biomarker, and it can assist predict benign or malignant in SPNs.